ANALISIS KECENDERUNGAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGAN DESA MENGGUNAKAN FRAUD DIAMOND THEORY (STUDI EMPIRIS DI KECAMATAN WORI) - Tinay, Agustinus; Karamoy, Herman; Sondakh, Jullie J. (Universitas Sam Ratulangi, 2022)
This study aims to empirically prove the influence of elements of fraud diamond theory bolawins, namely the influence of pressure, opportunity, rationalization and the capability of village officials to tend to fraud in village financial management in Wori Sub district, North Minahasa Regency. The approach used in this research is quantitative by using primary data through questionnaires. Respondents in this study were village financial management officers as many as 114 village officials in Wori sub-sub district, North Minahasa Regency. The data analysis technique uses multiple linear regression analysis using the SPSS program. The results of this study indicate that: 1). Pressure has a positive and significant effect on the tendency of fraud in village financial management in Wori Sub district, North Minahasa Regency. 2). Opportunity has a positive and significant effect on the tendency of fraud in village financial management in Wori Sub district, North Minahasa Regency. 3). Rationalization has a positive and significant effect on the tendency of fraud in village financial management in Wori Sub district, North Minahasa Regency. (4) The capability of village officials has a negative and significant effect on the tendency of fraud in village financial management in Wori Sub district, North Minahasa Regency.